EFFECT OF RECENT MOVEMENTS ON THE METHANE FIELD IN THE ATMOSPHERIC SURFACE LAYER - Sklyarenko I.Ya.; Stadnik Ye.V.; Feyzullayev A.A. (My University, 1989)
Numerous investigations have established the correlation between the gas regime of the earth's interior and geotectonic conditions expressed in near-surface parts of the crust and even in the atmospheric surface layer. In the present paper we discuss the distribution of methane in the atmospheric surface layer near the Krasnovodsk-Mary Railroad, where high-precision leveling was performed 3 times during a 20-year period (1944-1964). The method measurements were made with a high-sensitivity laser gas analyser mounted in an airplane. This example shows a clear dependence of the methane concentration in the atmospheric surface layer on the intensity of Recent vertical crustal movements: the zones of most pronounced Recent movements are associated with relatively high concentrations of methane in the atmospheric surface layer, and vice versa. This indicates the possibility that the spatial and temporal behavior of subvertical gas flows from the interior can be used as indicators of the character of Recent crustal movements.